Single element differentiation of chemical vapors using an array - Lee, Seok; Jung, Youngmo; Moon, Hi Gyu; Kang, Chong Yun; Kim, Chulki; Ha Woo, Deok; Kim, Sang Kyung; Jeong, Won Kyo; Shin, Jeonghun; Cho, Chang Ho; Lee, Taikjin (2018 INTERNATIONAL CONFERENCE ON ELECTRONICS, INFORMATION, AND COMMUNICATION (ICEIC), 2018)
We present a heterosensor array that exploits the collective recognition ability of a set of different gas sensors to identify individual chemical vapors. In contrast to the conventional sensing approach based on the 'flock-and-key" design, the heterosensor array rely on the response patterns produced over the collection of different sensors. Diverse sensors with different operating principles are employed to provide as much chemical diversity as possible. We demonstrate that this platform provides a highly discriminative tool with single element precision.